Integrating and Strengthening National Vision in the Community as an Effort to Prevent Radicalization and Foster Love for the Motherland - M. Furqon Al Maarif; Rizki Aprilia Nur Afifah; Adinda Choirunnisa; Afifah Miftahul Jannah; Muhammad Yusuf Zanuar; Kundharu Saddhono; Schunk Yingxiang (Pengabdian: Jurnal Abdimas, 2023)
Background. Efforts in awakening national values are efforts in building a nation. Pancasila as the ideology of the Indonesian nation is declining day by day. Many factors are suspected to be the cause, one of which is radicalization. As a form of effort in serving the community, the UNS MBKM Grant team, there is a Research Group on Indonesian Language, literature and culture trying to take part in efforts to prevent radicalization. Purpose. The purpose of this activity as an effort taken is to integrate and strengthen national insight in the community as an effort to prevent radicalization and foster love for the homeland which was carried out in Donorejo Village, Magelang. Service activities are carried out by dividing into three stages, namely the planning (plan), implementation (action), and evaluation (evaluation) stages. Method. The method used is PAR (Participatory Action Research). Service activities are carried out in various ways, among others, internationalization, example, habituation, humor, story attraction, advice and appreciation. The results of the service program are divided into 2 parts, namely short-term and long-term. Results. The implementation of national values will run effectively and intact if it involves three institutions, namely family, school and community. Conclusion. The life of the nation and state cannot be separated from various problems that arise. One of the problems was born as a result of the wider influence of globalization.